The Influence of Product Quality, Location, and Promotion on Consumer Purchase Decisions of Type 36 Houses at PT Maulana Wamahyaya Sejahtera in Kubu Raya Regency - Rapika Mayni; Muhammad Ebuziyya Alif Ramadhan (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to examine the influence of product quality, location, and promotion on consumer purchase decisions for Type 36 houses at PT Maulana Wamahyaya Sejahtera, Kubu Raya Regency. The research uses an associative method with a quantitative approach. Data were collected through interviews, questionnaires, and documentation, with a total sample of 101 respondents selected using purposive sampling. Data analysis techniques included validity and reliability tests, classical assumption tests, multiple linear regression analysis, as well as t-test and F-test. The results of the t-test show that product quality, location, and promotion have a significant effect on purchase decisions. These three independent variables have a positive and significant partial effect on consumer purchase decisions. Meanwhile, the F-test results indicate that product quality, location, and promotion simultaneously have a significant effect on purchase decisions. The coefficient of determination (R²) value of 0.745 indicates that 74.5% of the variation in consumer purchase decisions can be explained by these three variables, while the remaining 25.5% is influenced by other variables outside the scope of this study. These findings indicate that improving product quality, selecting strategic locations, and implementing effective promotional strategies can significantly enhance consumer purchase decisions for Type 36 houses at PT Maulana Wamahyaya Sejahtera.